The burden of over-representation : race, sport, and philosophy - Farred, Grant (Temple University Press, 2018)
"This book probes the cultural forces and legacies at play in three events in sports history, exploring how racial, national, sporting, and personal identities overlap and conflict. The author taps into a deep well of Western philosophy and literature to read the resonances in these three moments"--